2020
DOI: 10.1177/1557988320966540
|View full text |Cite
|
Sign up to set email alerts
|

“Is Life Worth Living?”: The Role of Masculinity in the Way Men Aged Over 80 Talk About Living, Dying, and Suicide

Abstract: Men aged 85 years and over have the highest rate of suicide of any age or gender group in Australia. However, little is known about their trajectory toward suicide. The objective of this study was to understand the role of masculine norms and other life factors in the suicidality of older men. Thirty-three men aged 80 years or more took part in a semistructured focus group or interview, and/or completed a survey. Participants were asked about the issues facing older men, well-being and aging, physical health c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…In addition, while there was a marked difference between C1 and C2 in SWEEMWBS at 12 months, results suggest that, despite COVID-19, Shedders retained an improvement in mental wellbeing as well as a sustained reduction in depression prevalence. It is widely accepted that men experience barriers with engaging in conversations about mental health, often exacerbated by social constructs of what it means to be ‘masculine’ [ 77 79 ]. This narrative has been challenged by research that highlights that when men are familiar with problem-solving strategies to maintain their mental wellbeing, they are open to using them [ 80 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, while there was a marked difference between C1 and C2 in SWEEMWBS at 12 months, results suggest that, despite COVID-19, Shedders retained an improvement in mental wellbeing as well as a sustained reduction in depression prevalence. It is widely accepted that men experience barriers with engaging in conversations about mental health, often exacerbated by social constructs of what it means to be ‘masculine’ [ 77 79 ]. This narrative has been challenged by research that highlights that when men are familiar with problem-solving strategies to maintain their mental wellbeing, they are open to using them [ 80 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…These differences extend to the experience of end-of-life (Hilário, 2015). Western masculine norms requiring the portrayal of strength, autonomy, and action may in part underlie their attitudes toward assisted dying (King et al, 2020). Attell (2020) concluded that support for euthanasia and suicide generally decreases as people age.…”
Section: Discussionmentioning
confidence: 99%
“…(Hudson et al, 2016, p. 4). Moreover, it has been suggested that older male respondents might adhere more strictly to norms on hegemonic masculinity (Campos-Castillo et al, 2020;King et al, 2020) and hence be less likely to show negative affect, whereas younger male respondents might be less worried about displaying their feelings out of fear of being considered vulnerable (Vogel et al, 2011). Thus, differences between age groups could be imputed not only to processes that occur over the life course (i.e., age affects), but also to different ways in which people were socialized as children (i.e., cohort and generational effects).…”
Section: Gender and Age Gaps In Feelings Emotions And Psycho-physiolo...mentioning
confidence: 99%